A logística reversa como instrumento da gestão de resíduos pós-consumo: uma análise do setor de telefonia móvel. - Lima, Maria do Carmo Ferreira (2008)
The growth of the mobile telephony sector in Brazil has increased the environmental impact due to the inadequate disposal of apparatus and cell phone accessories. On 30 June 1999, the National Council for the Environment (Conselho Nacional do Meio Ambiente - CONAMA) published the resolution number 257, which seeks the adequate disposal and environmental management of used batteries through collection, reutilization, recycling, treatment and final disposal. In this manner, the general objective of this dissertation was to verify the contribution of reverse logistics towards the management of post-consumption residues from the mobile telephony equipment. The research was carried out in two phases: the first one was an exploratory research to acquire data on mobile telephony to systematize informations concerning the theme and to get to know better the sector and the profile of the companies being studied, through consultation in their websites. In the next phase, a quantitative descriptive research through a survey was done using questionnaire application among a convenience sample of mobile telephony users. The results led to the following the mobile phone sector has become prominent due to its growth, with the expressive increase of users and, consequently, the environmental impacts of the sector have increased. A majority of the manufacturers informs about the disposal of the batteries after use, but none of them inform about the disposal of the cell phones and accessories. Regarding the issue is made aware of collection of batteries in the post-use, 81% of respondents replied that they had no such information. How to use post-discharge the battery, it is among other things that 17 respondents threw garbage in the house. And while operators and manufacturers meet the law 257/99 CONAMA this information does not appear to be clear and accessible enough for the user. In future studies it is suggested inserting Theory of Consumer Behavior.